Can social comparisons and moral appeals increase public transport ridership and decrease car use? - Johannes Gessner; Wolfgang Habla; Ulrich J. Wagner (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
In a field experiment with 341 participants, we study whether social comparisons, either in isolation or in combination with a climate-related moral appeal, can change the use of public and car-related transportation. We do so in the context of a mobility budget offered to employees of a large German company as an alternative to a company car. The budget can be used to pay for both leisure and commuting trips, and for various modes of transport. Behavioral interventions in this setting are of particular interest, since companies are constrained to significantly alter financial benefits to employees yet strive to lower carbon emissions via a shift to low-emission transport modes. We find strong evidence for a reduction in car-related mobility in response to the combined treatment, driven by reduced expenditures for taxi and UBER rides. This is accompanied by substitution towards micromobility, but not towards public transport. Furthermore, we do not find any effects of the social comparison alone. Our results demonstrate that norm-based nudges are able to change transportation behavior, at least temporarily.
urn:nbn:de:bsz:180-madoc-643121
Keywords: C93; D04; D91; L91; 330; mobility behavior; randomized experiment; nudging; descriptive norm; injunctive norm; social norms; moral appeal; habit formation